Bexley Responder: A Living Newspaper - Kargotis, Demetrios; Mortimer, Nicholas; Macdonald, Dash; Korda, Roxanne; Blanco, Daniel; Konat, Aparna (My University, 2024)
Bexley Responder: A Living Newspaper is a participatory, site-specific performance project developed by Post Workers Theatre in collaboration with Three Rivers. The project reactivates the historical form of the ‘Living Newspaper’, a mode of workers’ theatre emerging in the early twentieth century, to examine contemporary social issues through collective authorship and performance. Developed over a three-month period, the work engaged local residents in Bexley through story-gathering, co-writing workshops, and public interventions. Drawing on methods of practice-based research and co-creation, participants contributed to the development of episodic theatrical scenes based on locally relevant issues. The project explores how accessible forms of political theatre can be adapted to contemporary contexts, foregrounding community voice and shared authorship, while positioning performance as a tool for civic dialogue and engagement in public space.